Increased risk of colorectal cancer after cholecystectomy. - Turunen, M J (1981)
The relative risk of developing colorectal cancer after cholecystectomy has been assessed in a retrospective autopsy study using controls individually matched for age and sex. Of the 304 patients dying with colorectal cancer and undergoing autopsy examination at the Helsinki University Central Hospital, 45 had undergone previous cholecystectomy. The corresponding number for the matched-pair controls without colorectal cancer was 32, indicating that the relative risk of developing colorectal cancer is slightly (1.59), but significantly (p less than 0.05), increased after cholecystectomy. The relative risk was highest for cancer of the right colon (3.00). In contrast, no difference in the autopsy incidence of unoperated gallstones was observed between the two groups, suggesting that, rather than lithogenic bile alone, the predisposing factor is related to the cholecystectomy procedure itself.